New methods for assessing the impact of traffic safety countermeasures. - Christens, Peter Falck; Thyregod, Poul (Proceedings from the Annual Transport Conference at Aalborg University, 2003)
This paper investigates new methods for assessing the impact of traffic safety countermeasures on the number of accidents or injuries. The primary aim of this paper is to show in general how statistical methods that take development over time into account may be used when assessing the impact on traffic safety data. A secondary aim is to specifically investigate the effect of a change in the police accident reporting routine in 1997 on the injury classification. A salient characteristic in most monthly traffic safety data is a fluctuating trend and seasonal pattern. Some of the fluctuation can be explained, but in order to have a reliable assessment of the countermeasures the evaluation methods have to capture this fluctuation. So-called State Space models provide a framework, where these characteristics can be investigated and modelled explicitly. The change in the police reporting practice lead in 1998 to a 49% [35%; 60%] decrease in the reported number of head injuries in Copenhagen and in 1997 to a 37 % [27%, 46%] decrease outside Copenhagen. An estimate of the actual traffic safety in 1998 measured in the number of serious injuries could be the reported number corrected by an additional 670 injuries due to this change in the reporting.